3-D computational fluid dynamics modeling of a hollow fiber membrane contactor ozonation process. (February 2023) - Schmitt, Alice; Chevarin, Cyril; Mendret, Julie; Brosillon, Stephan; Bouyer, Denis
Abstract: Ozonation processes have been successfully used to remove organic micropollutants. Membrane contactors can transfer the ozone via a bubbleless process, making them promising devices for many applications thanks to a good control of the transferred ozone. Here we studied the local transfer of ozone into water through a single and a multi-fiber membrane contactor by developing a 3-D model in a Comsol Multiphysics® workflow. To our knowledge, this is the first model to combine 3-D analysis and a multi-fiber membrane contactor for an ozonation application. The model established here could serve as a startpoint for optimizing bubbleless processes and scaling up membrane contactor processes, including the ozonation of micropollutants. Dedicated experiments were performed to check the model. Using of a 3-D modeling approach makes it possible to account for the non-ideal effects that occur in hollow fiber membrane contactors. The simulations highlighted hydrodynamics as a very important factor to ensure good distribution of ozone and therefore good treatment of pollutants. Moreover, the transferred ozone does not increase proportionally with increasing membrane length or residence time. Finding the right compromise between contactor length and fibers number can help optimize the contactor geometry and thus make the process as effective as possible. Graphical abstract: Unlabelled Image Highlights: 3D modeling is needed to account for non-ideal effects in membrane contactors. Hydrodynamics is vital to ensure good distribution of ozone. Transferred ozone is not proportionally increased with increasing membrane length. A multi-fiber contactor offers better mixing and exchange surface than a single fiber. Optimization of the contactor design (length, number of fibers) is imperative.